Micropolar fluid flow and heat transfer over a nonlinearly stretching plate with viscous dissipation - Ahmad, Kartini; Ishak, Anuar; Nazar, Roslinda (Hindawi Publishing Corporation, 2013)
The flow and heat transfer of a micropolar fluid past a nonlinearly stretching plate is studied numerically, by taking into account the viscous dissipation effect. It is assumed that the plate is stretched nonlinearly from the slot where it is issued. The governing system of partial differential equations is transformed into ordinary differential equations, which are then solved numerically using a finite-difference scheme known as the Keller-box method.The effects of the governing parameters, namely, the material parameter K, the Eckert number Ec, the Prandtl number Pr, and the nonlinear stretching parameter n, on the flow field and the heat transfer characteristics are obtained and discussed. The velocity and the temperature profiles are also illustrated to aid the validity of the numerical results obtained. It is found that both the localNusselt number and themagnitude of the skin friction coefficient increase with the nonlinear stretching parameter n, and the opposite trend occurs as K increases for fixed n.